ANALISIS IMPLEMENTASI GOOD CORPORATE GOVERNANCE PADA KOPERASI DI KOTA DENPASAR - Gusti Ayu Asri Pramesti; Daniel Raditya Tandio (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2018)
The implementation of good corporate governance (GCG) is required by all business entities. This is very important because it involves transparency and accountability within a company. Deviations from the principles of good corporate governance will have an impact on the manipulation of information by the company. Cooperative is one of the business entities engaged in the field of economy which has always been based on the principle of kinship and economic democracy, because in the application of activities always try to prioritize the interests of its members based on common prosperity. Based on that, then in this research will describe how the implementation of good corporate governance in the cooperative contained in the city of Denpasar. Population in this research is cooperative exist in Denpasar city which amounts 1011 cooperatives. To determine the number of samples used Slovin formula, while the sampling technique used proportional random sampling. This sampling technique is used for the samples taken equally distributed in accordance with the proportions in the areas of North Denpasar, East Denpasar, South Denpasar and West Denpasar. The number of samples is 91 cooperatives.The results of this study is expected to provide an overview of the implementation of good corporate governance in the cooperative in Denpasar. This is very important because good governance is expected to maintain the operational sustainability of the cooperative in the future.